Survival of people aged 50 years and older by HIV and HIV treatment status: Findings from three waves of the SAGE-Wellbeing of Older People Study (SAGE-WOPS) in Uganda - Joseph Mugisha Okello (2020)
© 2020 The Author(s). Background: Data on the survival status of older adults on antiretroviral treatment (ART) are scarce in sub-Saharan Africa. The objective of this study was to determine the survival status of people aged 50 years and older who were HIV-negative, HIV-positive not on ART, and HIV-positive on ART. Methods: We used three waves of data from the World Health Organisation Study on Global Ageing and adult health-Well Being of Older People Study cohort in Uganda, conducted in 2009, 2012-2013 and 2015-2016. The cohort included HIV-negative and HIV-positive persons aged 50 years and older recruited from multiple rural and peri-urban sites in Uganda. Data were collected using interviewer-administered questionnaire. Time-dependent ART data were collected from medical records using a data-abstraction form. This study was conducted before the universal test and treat policy came into effect. We fitted Cox survival models to estimate hazard ratios to compare the risk of death between groups, adjusted for age, sex, marital status and hypertension. Results: Of 623 participants, 517 (82.9%) of respondents had follow-up data and were included in this analysis. We observed 1571 person-years of follow-up from 274 people who were HIV-negative, and 1252 from 243 who were HIV-positive. The estimated mortality adjusted hazard ratio (aHR) was 1.89 (95% CI 1.0-3.4; p = 0.04) among people living with HIV compared to HIV-negative people. The aHR for mortality among people receiving ART compared with HIV-negative people was 1.75 (95% CI 0.9-3.5). People who were HIV-positive and not receiving ART had the greatest risk of death (aHR = 2.09, 95% CI 1.0-4.4 compared with HIV negative participants). The aHR for HIV-positive people not receiving ART, compared to those who were on treatment, was 1.19 (95% CI 0.6-2.5). Conclusion: Older adults living with HIV on ART had a risk of mortality that was nearly twice as high as HIV-negative adults. Further analyses of longitudinal data should be done to understand factors that affect the survival of older adults on ART.